Use of 3-D Plate in Displaced Angle Fracture of Mandible - Pal, Uma Shanker (Thieme Medical Publishers, 2013)
Introduction Mandibular angle fractures can be treated by various methods, but even the most popular methods may not be able to give satisfactory results, as the pterygomasseteric sling and masticatory forces can result in displaced angle fracture. These displaced fragments cannot be satisfactorily retained by single miniplate fixation. The aim of this study is to assess treatment of displaced angle fracture with 3-D miniplate fixation. This study can also be considered as a therapeutic study with level V evidence. Materials and Methods This study was designed to assess the feasibility of 3-D matrix miniplate fixation in displaced angle fractures. Eighteen patients with displaced angle fractures were included in this study. Matrix miniplate fixation was done transorally under general anesthesia. Results All these cases were treated successfully, and common complications like infection (5.5% of patients), wound dehiscence (11%), paresthesia (16.7%), and malocclusion (11%) were observed in our study. Conclusions Three-dimensional miniplate fixation in displaced angle fractures provides better stability and function.